Activity of Lipoperoxidation – Antioxidant Protection Reactions in Patients with HIV Infection (Review) - O. A. Nikitina (Acta Biomedica Scientifica)
Changes in the activity of the lipid peroxidation – the antioxidant defense system is an important metabolic  characteristic in various diseases, including infection with the human immunodeficiency virus. The high  medical, social and economic significance of HIV infection is determined by the widespread and severe course of the disease. Up to 2.7 million new infections are registered in the world every year. The increase in the  prevalence of HIV infection in the Russian Federation is largely due to the prevalence of sexual transmission (50.3 %). In recent years, the proportion of women of reproductive age who are infected with HIV has significantly increased, which entails the problem of an increase in the number of cases of HIV transmission from mother to child during pregnancy and childbirth.According to a number of authors, it was found that in patients with HIV infection there is an intensification of the processes of lipid peroxidation, against the background of depletion of the activity of the antioxidant defense system. The presence of co-infections in the human immunodeficiency virus, concomitant diseases and other negative factors can aggravate the course of this kind of reactions.The article presents a review and analysis of recent literature data on studies of the features of changes in free radical oxidation indicators in HIV infection. The study of LPO–AOD processes in HIV infection is necessary and can act as a new approach in the prevention of complications and treatment of this disease.When writing the review, the database of the scientific electronic library (eLibrary.Ru) was used, the keywords were HIV, lipid peroxidation, lipid peroxidation, free radical oxidation, antioxidant protection; filters: publication years 2010–2020, publications with full text, publications available for viewing; An English-language database of medical and biological publications created by the NCBI, keywords: HIV, lipid  peroxidation, antioxidant protection, antioxidants, oxidative stress, human immunodeficiency virus.